Structural evolution, site ordering and magnetic properties of tetragonal Mn6‐yGa2+y (0 ≤ y ≤ 1.64). (1st March 2017) - Zhao, Hui; Yang, Wenyun; Shao, Zhuyin; Tian, Guang; Zhou, Dong; Du, Honglin; Liu, Shunquan; Han, Jingzhi; Wang, Changsheng; Xu, Jing; Yu, Dunbo; Yang, Yingchang; et al.
Abstract: A D022 -type super structure with a formula Mn6‐y Ga2 + y (0 ≤  y  ≤ 1.64) is proposed to describe the structural evolution of tetragonal Mn3‐x Ga (0 ≤  x  ≤ 1.8) intermetallic compounds. Degree of site disorder is obtained based on the 2 b -site Mn and 2 a -site Ga disordering model. Neutron data refinement indicates that the structure transforms from a completely ordered state ( y  = 0) to the 2 a and 2 b sites (Mn-Ga) disordered state ( y  > 0.92) with increasing y . The ferrimagnetic ordering structure between Mn (4 d ) and Mn (2 a /2 b ) has been established, with the magnetic moment retaining almost 2.2  μ B and ranging from − 3.3  μ B ( y  → 0) to − 2.3  μ B ( y  → 1.64), respectively. Graphical abstract: